2021
DOI: 10.1155/2021/8451241
|View full text |Cite
|
Sign up to set email alerts
|

Damages of Underground Facilities in Coal Mines due to Gas Explosion Shock Waves: An Overview

Abstract: With coal mining depth increase, gas explosion accidents due to the high gas emission rates often occur which cause significant casualties and property damages. Among them, gas explosion shock waves not only can destroy the machines and equipment in mine roadways but also cause the failure of mine ventilation facilities resulting in secondary hazards. Thus, the mines’ serious disasters could happen. For many years, researchers have already done a great lot of works to study damages caused by the impact of shoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…During normal operations, the ventilation system supplies fresh air, diluting and drawing out the heat, dust, and hazardous gases [19]. A failure of the ventilation system can therefore lead to major accidents, with damage to equipment, property, and even fatalities [20,21]. In the case of a ventilation system failure, a gas monitoring system could detect the build-up of hazardous gases and warn the mine operators, enabling them to react to the situation before any incidents take place [19].…”
Section: Underground Mine Hazardous Gas Monitoring Literature Reviewmentioning
confidence: 99%
“…During normal operations, the ventilation system supplies fresh air, diluting and drawing out the heat, dust, and hazardous gases [19]. A failure of the ventilation system can therefore lead to major accidents, with damage to equipment, property, and even fatalities [20,21]. In the case of a ventilation system failure, a gas monitoring system could detect the build-up of hazardous gases and warn the mine operators, enabling them to react to the situation before any incidents take place [19].…”
Section: Underground Mine Hazardous Gas Monitoring Literature Reviewmentioning
confidence: 99%
“…With the utilization of coal resources, the mining intensity increases year by year, and the underground mining conditions become more complex, resulting in an increase in disasters and accidents, such as fires, explosions, and outbursts. , After a coal mine disaster, the rapid sealing and isolation control of the disaster area can effectively prevent further accidents. , To improve the mine emergency response ability to deal with disasters and accidents, scholars conducted relevant research on the technology and equipment for rapid closed isolation of disaster areas after disasters. Chang proposed a solidified door structure for a mine rescue cabin, established a three-dimensional model of a mine mobile protective closed door, and analyzed the strength of an arc door with ANSYS software. The results showed that the strength and stiffness of the arc door are better than those of the ordinary flat door.…”
Section: Introductionmentioning
confidence: 99%
“…With the utilization of coal resources, the mining intensity increases year by year, and the underground mining conditions become more complex, resulting in an increase in disasters and accidents, such as fires, explosions, and outbursts. 1 , 2 After a coal mine disaster, the rapid sealing and isolation control of the disaster area can effectively prevent further accidents. 3 , 4 To improve the mine emergency response ability to deal with disasters and accidents, scholars conducted relevant research on the technology and equipment for rapid closed isolation of disaster areas after disasters.…”
Section: Introductionmentioning
confidence: 99%